The hsa_circRNA_102049 mediates the sorafenib sensitivity of hepatocellular carcinoma cells by regulating Reelin gene expression. Issue 2 (1st February 2022) - Wang, Shaolei; Liu, Dehua; Wei, Hong; Hua, Yang; Shi, Guodong; Qiao, Jinhan
ABSTRACT: A growing body of research has illuminated that non-coding RNAs (ncRNAs) plays an important role in the development of drug resistance in hepatocellular carcinoma (HCC) cells. The expression profiles of differential expressed genes (DEGs) and ncRNAs related to the sorafenib resistance in HCC cells were analyzed according to the Gene Expression Omnibus (GEO) dataSets and The Cancer Genome Atlas (TCGA) datasets. Bioinformatics technology was used to construct the interaction network of DEGs and ncRNAs. Cell transfection, dual-luciferase reporter assay, Western blot, cell counting kit-8 (CCK-8), flow cytometry and quantitative real-time polymerase chain reaction(qRT-PCR) were used to study the mechanism of sorafenib resistance in HepG2 cells and Huh-7 cells. The expression of reelin (RELN) and secretagogin (SCGN) were the only down-regulated in sorafenib-resistant HCC cells. The results showed that RELN gene demethylation reversed the cytotoxic of sorafenib on HepG2 cells and Huh-7 cells. Hsa_circRNA_102049 over-expression promoted the sensitivity of HepG2 cells and Huh-7 cells to sorafenib, hsa_circRNA_102049 up-regulated the expression of RELN gene by sponging hsa-miR-214-3p. The resistance to sorafenib in RELN knockout HepG2 cells and Huh-7 cells could be reverted by has-circRNA_102049. These findings support targeting of hsa_circRNA_102049 and RELN in sorafenib-treated HCC cells as a novel intervention, which is expected to overcome sorafenib resistance of HCC cells. GRAPHICAL ABSTRACT: uf0001